The evolution of technical analysis : financial prediction from Babylonian tablets to Bloomberg terminals - Lo, Andrew W.; Hasanhodzic, Jasmina (Hoboken, N.J. : John Wiley & Sons, 2010)
The book explores the history of technical analysis from ancient Babylon through the Internet Age, and highlights the successes and failures of the pioneers - the famous and forgotten - who played a pivotal role in the evolution of this fascinating craft.
Includes bibliographical references (p. 191-197) and index.
rua 22/05/13
Loans
Keywords: Technical analysis (Investment analysis)